Effects of supplementing sow diets with fermented corn and soybean meal mixed feed during lactation on the performance of sows and progeny. (25th January 2018) - Wang, C; Lin, C; Su, W; Zhang, Y; Wang, F; Wang, Y; Shi, C; Lu, Z
Abstract: In the present study, two experiments were performed to study the effects of feeding fermented corn and soybean meal mixed feed (FMF ) with Bacillus subtilis and Enterococcus faecium to lactating sows on the performance of the sows and their progeny. In experiment 1, 60 sows were allocated to the following three dietary treatments: 1) sows fed a corn and soybean meal basal diet (control) from day 3 before parturition to weaning, 2) sows fed a diet with 7.5% FMF, and 3) sows fed a diet with 15% FMF. Results indicated that feeding 15% FMF significantly improved ( P < 0.05) the sows' ADFI, the individual piglet weaning weights, and piglet weight gain and reduced ( P < 0.05) the backfat loss of sows compared with the control group. However, the 7.5% FMF treatment did not alter the performance of the sows or their progeny. Therefore, we considered the level of 15% FMF to be more efficient than 7.5% FMF. To verify the results of experiment 1, we performed experiment 2, in which 60 sows at 111 d of gestation were allocated into the following two dietary treatments: 1) sows fed a basal lactation diet (control) from d 111 of gestation to weaning and 2) sows fed a basal diet with 15% FMF. Compared with the control group, 15% FMF inclusion significantly increased ( P < 0.05) the sows' ADFI, litter weight gain, and individual piglet weight gain during lactation and markedly decreased the backfat loss of sows ( P < 0.05) and piglet diarrhea incidence ( P < 0.05). Additionally, the milk yield and IgA contents of the milk in sows fed 15% FMF were greater ( P < 0.05) than those of the control group. Furthermore, the apparent total tract digestibility of GE, DM, and total P of sows was increased ( P < 0.05) with 15% FMF supplementation. Therefore, the present study indicates that supplementing sow diets with 15% FMF from parturition to weaning has the potential to 1) increase sow ADFI, milk production, milk IgA content, and nutrient digestibility and promote sow reproductive performance by shortening the weaning-to-estrous interval and 2) promote the growth performance of their progeny and decrease diarrhea incidence.